Isolation, identification and investigation of some properties of Lacticaseibacillus rhamnosus 1 for application in the composition of probiotics - Denkova Zapryana; Zapryanova Polina; Denkova-Kostova Rositsa; Goranov Bogdan; Urshev Zoltan; Gaytanska Yordanka; Shopska Vesela (BIO Web of Conferences)
The introduction of lactic acid bacteria into the composition of probiotics requires the constant isolation and identification of new strains isolated from natural sources or spontaneously fermented products, the study and characterization of their properties and the selection of strains with proven probiotic properties. Strain 1, isolated from spontaneously fermented pasteurized milk, was identified by applying physiological-biochemical (API 50 CHL) and molecular-genetic methods (16S rRNA gene sequencing) as a representative of the species Lacticaseibacillus rhamnosus. Some of its potentially probiotic characteristics and its enzymatic profile were determined. Lacticaseibacillus rhamnosus 1 was resistant to antibiotics, inhibitors of cell wall synthesis, but was sensitive to most representatives of the other two groups of antibiotics: inhibitors of protein synthesis and inhibitors of DNA synthesis and/or cell division. The strain inhibited the growth of pathogenic microorganisms (Escherichia coli, Staph. aureus, Salmonella abony, Enterococcus faecalis, Ps. aeruginosa) and the majority of saprophytic microorganisms (Bacillus subtilis, Bacillus cereus, Mucor luteus, Rhizopus oryzae, Aspergillus niger, Fusarium moniliforme) included in the study. Lacticaseibacillus rhamnosus 1 exhibited high proteolytic and amylolytic activity. Lacticaseibacillus rhamnosus 1 has some probiotic properties and after further investigation of other probiotic properties, it can be included in the composition of probiotic preparations.